Cooperation Achieves Optimal Multicast Capacity-Delay Scaling in MANET - Wang, Xinbing; Peng, Qiuyu; Li, Yingzhe (IEEE transactions on communications, 2012)
In this paper, we focus on capacity-delay tradeoffs for multicast traffic pattern. Under the assumption that n nodes move in a unit square according to an i.i.d. mobility model, with each serving as a source that sends identical packets to k destinations, we propose four schemes of which the achievable capacity λ and delay D are analyzed: (1) 2-hop noncooperative non-redundancy scheme, (2) 2-hop noncooperative redundancy scheme, (3) 2-hop cooperative non-redundancy scheme, (4) 2-hop cooperative redundancy scheme. Compared with non-cooperative scheme with capacity delay tradeoff λ = O( E[D]/nk log k) first developed in [5], cooperation among destination nodes achieves optimal capacity delay tradeoff λ = O(E[D]/n log k) in cell partitioned network. With intelligent cooperation, each destination acts equivalently as relay and helps other destinations get more opportunities of receiving packets with capacity sacrificed to a addition, our redundancy schemes also allow delay under Θ(√n) log k factor compared with unicast in [3] under the same delay. In achievable, which is the minimum delay under the schemes of [3],[5].